Influence of a complex disease involving Praylenchus goodeyi and a nonpathogenic strain of Fusarium oxysporum on banana root health - Speijer, P.; Sikora, R.A. (1994)
Studies were undertaken to determine disease interactions involving P. goodeyi and a non-pathogenic strain of F. oxysporum, both responsible for root-rotting and subsequent toppling of 2 banana cultivars in Kenya. Thirty days after inoculation of young banana plants with P. goodeyi alone or in combination with F. oxysporum the higher density of P. goodeyi was found in necrotic primary roots of the cultivar Nakyetengu (AAA). In primary roots of the cultivar Sukali Ndizi (AB) high density of P. goodeyi was associated with necrosis only in combination with F. oxysporum. In secondary roots of Nakyetengu high density of P. goodeyi associated with necrotic root tissue was only observed when P. goodeyi was inoculated without additional F. oxysporum species. Necrosis and high density of P. goodeyi were associated in secondary roots of Sukali Ndizi independent of the addition of F. oxysporum spores to the inoculum suspension. The results demonstrated a cultivar dependent interrelationship between the nematode and the fungus in a root-rotting complex.